Fish welfare: Improving fish culture method through modification of the light conditions - Mukai, Yukinori; Saad, Shahbudin; Muhammad, Firdaus Sallehudin (2016)
God creates fish for the benefit of humankind. For many centuries, fish has been vastly captured and cultured by human to fulfill the demand for food. Besides that, fisheries and aquaculture contribute to the social and economic development of the nation. However, in culturing fish, human tends to overlook the welfare of the fish. Most of the time, fish are exposed to varieties of stressor that can affect their health and reduce their survival and growth rates. As human are encouraged to treat animals including fish with compassion and love, it is important to provide optimum and less stressful conditions in culturing fish. Moreover, fish welfare is an important issue in aquaculture industry, not only for public perception, marketing and product acceptance, but also often in terms of production efficiency, quality and quantity. One of the methods that can be used to improve fish culture environment is through modification of light conditions. Two of the light characteristics that can affect the survival, growth and stress response of the fish are light intensity and light wavelength. Therefore, in this paper, the effects of light intensities and light wavelengths on fish were reviewed to determine the optimum light condition for fish. This information will help fish farmers to improve their fish culture method which in return increase the fish health quality and production.